Overexpression of the CC-type glutaredoxin, OsGRX6 affects hormone and nitrogen status in rice plants - El-Kereamy, Ashraf; Bi, Yong-Mei; Mahmood, Kashif; Ranathunge, Kosala; Yaish, Mahmoud W.; Nambara, Eiji; Rothstein, Steven J. (Frontiers in Plant Science, 2015)
Glutaredoxins (GRXs) are small glutathione dependent oxidoreductases that belong to the Thioredoxin (TRX) superfamily and catalyze the reduction of disulfide bonds of their substrate proteins. Plant GRXs include three different groups based on the motif sequence, namely CPYC, CGFS and CC-type proteins. The rice CC-type proteins, OsGRX6 was identified during the screening for genes whose expression changes depending on the level of available nitrate. Overexpression of OsGRX6 in rice displayed a semi-dwarf phenotype. The OsGRX6 overexpressors contain a higher nitrogen content than the wild type, indicating that OsGRX6 plays a role in homeostatic regulation of nitrogen use. Consistent with this, OsGRX6 overexpressors displayed delayed chlorophyll degradation and senescence compared to the wild type plants. To examine if the growth defect of these transgenic lines attribute to disturbed plant hormone actions, plant hormone levels were measured. The levels of two cytokinins (CKs), 2-isopentenyladenine and trans-zeatin, and gibberellin A1 (GA1) were increased in these lines. We also found that these transgenic lines were less sensitive to exogenously applied GA, suggesting that the increase in GA1 is a result of the feedback regulation. These data suggest that OsGRX6 affects hormone signaling and nitrogen status in rice plants.